Corncob :A comfort to laboratory rodents or A risk to research objectives ? (Journal of Laboratory Animal Science, 2024)
Corncob has been the most common choice of bedding material for laboratory animals in many countries due to its ready  availability, low cost and better absorbance properties. However, corncob has been reported to have estrogenic, endocrine  disruption and mitogenic properties by few authors. Animal facilities need to make a wise decision while selecting a  particular bedding type, such that the unwanted effects associated with bedding like corncob, may not interfere with  the research objectives. Chip bedding made from hardwood is one of the most common choices of bedding by most  international animal facilities for commercial breeders, academic research institutes, pharmaceutical industry and pre clinical contract research organisations.
Keywords: Corncob; estrogenic; endocrine disruption; mitogenic; hardwood chips